2014
DOI: 10.1088/1612-2011/11/12/125806
|View full text |Cite
|
Sign up to set email alerts
|

Power scale-up and propagation evolution of structured laser beams concentrated on 3D Lissajous parametric surfaces

Abstract: We systematically explore the power scale-up and propagation evolution of Lissajous structured beams in a lowly Nd-doped YVO 4 laser with the off-axis pumping scheme. We experimentally found that the average output power can be up to 1.0 W for the output transmission in the range of 1.8-10% at an incident pump power of 6.2 W. It is also found that when the output transmission is greater than 5%, the spatial coherence is considerably reduced to lead to a feature of broken Lissajous figures in transverse pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…It has been demonstrated that Lissajous geometric modes can be well generated from an off-axis diode-end-pumped Nd:YVO 4 laser. The detailed description for the experiment can be obtained from previous papers [14,40,41]. When a short laser crystal with length of 1~2 mm was used in experiment, the value of M was found to be greater than 300 by far.…”
Section: Experimental and Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that Lissajous geometric modes can be well generated from an off-axis diode-end-pumped Nd:YVO 4 laser. The detailed description for the experiment can be obtained from previous papers [14,40,41]. When a short laser crystal with length of 1~2 mm was used in experiment, the value of M was found to be greater than 300 by far.…”
Section: Experimental and Numerical Resultsmentioning
confidence: 99%
“…One of the most striking geometric modes is the transverse intensities exhibiting the Lissajous figures [31][32][33][34][39][40][41]. In 1964, Herriot et al [42] proved that under foldback conditions, an incident laser beam can be reflected forth and back between two spherical mirrors to exhibit an elliptical pattern.…”
Section: Introductionmentioning
confidence: 99%
“…which can be used in freely trapping of multiple particles [21]. Y. F. Chen et al has realized plenty of geometric modes with peculiar profiles of multiple circles [22], Lissajous parametric surfaces [23], [24], quantum Green's functions [25], [26], and multiple spots shape [27]- [29], which all reveal a deeper quantum-classical connection as quantum coherent states in SU(2) Lie algebra [30]- [33]. To sum up, the investigations upon novel structured vortex light fields are of great significance for frontier scientific researches.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial shaping of a light field to promote certain desired features during propagation has become an attractive problem with wide and increasing applications across several disciplines. For instance, theoretical and experimental studies have been directed toward the fundamental physics of the Lissajous beams, whose intensity distributions are well concentrated along the Lissajous curves [1][2][3][4][5][6]. Because of of the McGCSM beam is capable of generating far field with fully controllable square optical lattice consisting of Gaussian-like individual spots.…”
Section: Introductionmentioning
confidence: 99%
“…Some make use of the folded optical path between a pair of spherical mirrors [1], and some take advantage of the Nd:YVO 4 laser with a doughnut-shape pumped profile [2,3]. Lately, Chen et al developed an off-axis pumping scheme in which a Nd:YVO 4 laser with degenerate cavities was used to form three-dimensional coherent beams localized on Lissajous parametric surfaces [4][5][6]. They further demonstrated that the Lissajous-structured beams generated in their case are induced by the longitudinal-transverse coupling and can be expressed as a coherent superposition of various degenerate Hermite-Gaussian modes [4].…”
mentioning
confidence: 99%